Rising energy prices and productivity: short-run pain, long-term gain? - André, Christophe (OECD Publishing, 2023)
Soaring energy prices have raised concerns about the risks energy price shocks pose for firms' performance and the green transition. This paper estimates the impacts of energy price changes on firms' productivity as well as their dynamics, distinguishing between the short and medium-to-long term, using historical data. The analysis shows that following an energy price shock, firms adjust down their capacity utilisation, and their productivity declines. The estimates suggest that a 5% increase in energy prices reduces productivity by approximately 0.4% one year later. However, firms may display positive productivity gains in the medium term. Specifically, a shock corresponding to a 10% increase in energy prices is associated with an increase in productivity growth of around 0.9 p.p four years after the shock. These gains are more likely in less energy-intensive sectors, but tend not to materialise for larger shocks. There is some evidence that investment may be the channel behind productivity gains, the latter being larger for firms that had made investments in capital just before the shock
Keywords: Economics